The effects of climate change on gender roles among agro-pastoral farmers in Nabilatuk district, Karamoja subregion, North Eastern Uganda - Ayub, Mukisa; Muhanguzi, Florence Kyoheirwe; Boonabaana, Brenda (Frontiers in Human Dynamics, 2023)
This study examines the effects of climate change on gender roles among agro-pastoral farmers in Nabilatuk District, Karamoja subregion, in North Eastern Uganda. Data were collected from 10 focus group discussions, 10 key informant interviews, and observations. Atlas Ti 7.5.18 software was used to analyze the data. Findings indicate that climate change has disrupted traditional gender roles among men and women in Karamoja. Because of this, men have been forced to shift from pastoralism to crop farming. Additionally, some men have taken on reproductive roles that were formerly female-dominated. Women, on the other hand, have taken on petty trade in trading centers, which was formerly only a men's pursuit. This has come as an increased workload for women, leaving them even more vulnerable. This shift brings into question the notion of the stability of gender roles and how this affects the agricultural productivity of both men and women. Conclusively, there is a need for the adaptation of gender-sensitive strategies that can reduce the work burden of women.